Conformationally Restricted Peptides from Rice Proteins Elicit Antibodies That Recognize the Corresponding Native Protein in ELISA Assays - Barrera, Nubia F.; Melgarejo, Luz M.; Cruz Gallego, Maribel; Cortés, Lina Jimena; Guzmán, Fanny; Calvo, Julio C. (MDPI, 2018)
The rice hoja blanca virus (RHBV), transmitted by the planthopper insect Tagosodes orizicolus, is a disease that attacks rice and generates significant production losses in Colombia. Fedearroz 2000 and Colombia I commercial rice varieties, which have different resistance levels to the disease, were selected in this study. To identify proteins associated to the insect and virus signaling, a comparative proteomics study was performed. By comparing proteomic profiles, between virus-infected and control group plants in two-dimensional electrophoresis, proteins exhibiting significant changes in abundance were found. In another test, peptide dendrimers containing sequences conformationally restricted to α-helix from four of those rice proteins were synthesized. In the experiment, sera from mice inoculated with peptide dendrimers could recognize the corresponding native protein in ELISA assays. Reported comparative proteomic results provide new insights into the molecular mechanisms of plant response to the RHBV and comprehensive tools for the analysis of new crop varieties. Besides, results from conformational peptide dendrimer approach are promising and show that it is feasible to detect proteins as markers, and may have biological applications by decreasing the susceptibility to proteolytic degradation.